2022
DOI: 10.1002/jcla.24747
|View full text |Cite
|
Sign up to set email alerts
|

Association between IL1RL1 gene polymorphisms and allergic rhinitis risk in the Chinese Han population

Abstract: Background Although it has been confirmed that IL1RL1 is involved in the occurrence of allergic rhinitis (AR), the role of IL1RL1 gene single nucleotide polymorphisms (SNPs) in AR is still unclear. Methods We performed a case–control study including 1000 AR patients and 1000 healthy controls. The four SNPs rs72823628 G > A, rs950881 G > T, rs72823641 T > A and rs3771175 T > A in IL1RL1 were chosen and genotyped using Agena MassARRAY platform. The relationship between IL1RL1 SNPs and AR risk was analyzed by log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Based on these results, we classified AR into two robust subtypes, AR1 ( n = 21) and AR2 ( n = 18). We found that most of the immune- and cytokine-related signatures were significantly altered between AR1 and AR2 ( Figure 2(d) ), revealing a gradual increase in the expression of top genes and rhinitis marker genes (e.g., IL1RL1 , CD274 , and CD44 ) from healthy controls to AR1 and then AR2 ( Figure 2(e) ) [ 19 , 20 ]. When we calculated the enrichment score (ES) for each group on the differentially expressed genes of immune cell-related signatures (Supplementary Table 4 ), we observed significantly higher ES of monocyte and dendritic cells in AR2 samples than other groups ( P < 0.001, one-way ANOVA test, Figure 2(f) ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these results, we classified AR into two robust subtypes, AR1 ( n = 21) and AR2 ( n = 18). We found that most of the immune- and cytokine-related signatures were significantly altered between AR1 and AR2 ( Figure 2(d) ), revealing a gradual increase in the expression of top genes and rhinitis marker genes (e.g., IL1RL1 , CD274 , and CD44 ) from healthy controls to AR1 and then AR2 ( Figure 2(e) ) [ 19 , 20 ]. When we calculated the enrichment score (ES) for each group on the differentially expressed genes of immune cell-related signatures (Supplementary Table 4 ), we observed significantly higher ES of monocyte and dendritic cells in AR2 samples than other groups ( P < 0.001, one-way ANOVA test, Figure 2(f) ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study demonstrated that genetic variations in IL1RL1 are strongly associated with asthma, revealing that IL1RL1 acts as an essential driver of type 2 immune responses to IL-33 [ 29 ]. Moreover, IL1RL1 is a reliable marker of Th2 lymphocytes in AR, and IL1RL1 variants (e.g., rs72823628, rs950881, and rs3771175) are associated with AR risk [ 19 , 30 , 31 ]. However, in this study, the association of these variants and others between AR1 and AR2 was not identified, which is a limitation of this study and should be confirmed in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Faber et al found a genetic association between rs1921622 in IL1RL1 and disease severity in respiratory syncytial virus bronchiolitis ( Faber et al, 2012 ). IL1RL1 polymorphisms rs72823628, rs950881 and rs3771175 were found to be associated with a reduced risk of allergic rhinitis risk in the Chinese Han population ( Li et al, 2022 ). However, there are few studies on the correlation between IL1RL1 polymorphisms and lung cancer susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we downloaded ped and info files of mutation sites in IL1RL1 in the Chinese Han Beijing (CHB) population from 1000 Genome Project through VCF to PED Converter window ( http://grch37.ensembl.org/Homo Sapiens/Tools/VcftoPed), and we used Haploview software to screen SNPs with Hardy-Weinberg equilibrium (HWE) > 0.05, minor allele frequency (MAF) > 0.05, and min genotype frequency >75%, r 2 > 0.8. Finally, based on previous studies associated with respiratory diseases ( Ferreira et al, 2011 ; Shrine et al, 2019 ; Sun et al, 2019 ; Wu et al, 2021 ; Li et al, 2022 ; Rojo-Tolosa et al, 2023 ) and primer design, a total of six SNPs in the IL1RL1 gene were randomly selected ( Supplementary Table S1 ). The potential role of SNPs was predicted using RegulomeDB ( https://regulomedb.org/ ), HaploReg ( https://pubs.broadinstitute.org/mammals/haploreg/haploreg.php ), and Genotype-Tissue Expression (GTEx) Portal databases ( https://gtexportal.org ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation